Angewandte Linguistik für Sprachberufe - Perrin, Daniel (De Gruyter Studium, 2022)
This volume introduces applied linguistics for language-based professions. Learning and practicing with both book and an online offering promotes academically rigorous thinking and action in everyday professional life, which is increasingly being shaped by artificial intelligence. This second edition contains new, updated exercise materials that provide in-depth illustrations, documentation, and reflections on existing basic knowledge.